Legal field of the institution of constitutional review: past and present - Beibitov, M.S.; Taitorina, B.A.; Baisalova, G.T.; Azretbergenova, I.Zh. (Bulletin of the Karaganda University “Law Series”, 2020)
The article considers a historical retrospective of the formation and development of constitutional control in the context of the traditions of constitutionalism. The phenomena of constitution, constitutionalism, constitutional control are analyzed in the hypostasis of the most important attributes of any democratic, progressive state. The tendency of the modern period of the development of constitutionalism is highlighted — a twovector characteristic: in the paradigms of practical and theoretical constitutionalism. It is subjected to the analysis and theoretical justification of the multifaceted interpretation of the meaning of constitutional control. To achieve the goal of the study, the authors of the article subjected to the conceptual analysis the genesis and evolution of the institution of constitutional control in the world practice of constitutionalism. Based on theoretical sources and empirical material, the problems of the emergence and development of a state-legal institution are investigated: legal concepts, sources of organization and functioning of varieties of models of constitutional control existing in the modern period in the countries of the world. Based on the periodization of the evolution of the institution of constitutional review in the countries of the world, the main trends and specific features of the development of this institution at all stages of historical development are characterized. As a result of summarizing the achievements of world practice, three main models of constitutional control are distinguished: American, continental and mixed.The authors of the study substantiated the real significance for domestic constitutionalism of creating in practice the system of constitutional control of the Republic of Kazakhstan.